Sensory properties and consumer acceptance of plant-based meat, dairy, fish and eggs analogs: a systematic review - Appiani, Marta; Cattaneo, Camilla; Laureati, Monica (Frontiers in Sustainable Food Systems, 2023)
Introduction: Over the past years, several efforts have been made to formulate and develop plantbased substitutes of animal-based products in response to environmental changes, health issues and animal welfare. However, plant-based protein poses several challenges to product sensory characteristics, especially appearance, flavour and texture. Despite this, current literature data have mainly reviewed nutritional, technological and sustainability aspects of plant-based products with limited concerns on perceived sensory properties and perceptive barriers to consumption related to each specific substitute. To fill this literature gap, this systematic review aims to provide an up-to-date overview of the perceptive determinants of consumers' acceptance of plant-based substitutes of animalorigin products, including meat, dairy, fish and eggs analogues, with emphasis on product's intrinsic properties: appearance, smell, taste and texture. Moreover, age-, gender-, and cultural-related differences in the appreciation/rejection of plant-based substitutes of animal-origin products were investigated. Methods: The systematic analysis of the literature consulting Web of Science (Core Collection) and Scopus databases retrieved 13 research articles on meat, 26 on dairy and 2 on fish and eggs analogues. Results and discussion: Results showed that all sensory dimensions are influenced by the replacement of animal proteins with those of vegetable origin. However, the relative importance of appearance, odour, taste and texture varied according to plant-based analogues category and mitigatory processing strategies to mask unpleasant sensory properties have been suggested for each category. Dairy analogues mainly suffer of aromas and flavours imparted by the raw materials, while both meat and dairy analogues have texture challenges. Meat analogues lack of juiciness, elasticity and firmness, while dairy analogues require uniform, creamy and thick texture. Moreover, very few studies analysed the product's perception, considering age-and gender-related differences or crossnational/cultural differences. Future research should be addressed to specific product categories such as fish and eggs analogues as well as specific population targets including children and the elderly and consumers from developing countries.